De servidores a trabalhadores: as condições de trabalho dos funcionários técnico-administrativos da Unesp - Nunes, Janaína Gonçalves (2016)
This research aimed to identify the working conditions of technical and administrative workers at UNESP - Universidade Estadual Paulista (State University of São Paulo). To this end, we addressed in our theoretical framework the totality of issues that are directly related to the researched object, such as changes promoted by the structural crisis of capital in the economic sphere, with repercussions on the world of work through the restructuring process, also in the political sphere, with neoliberalism and in the sphere of culture, with conservatism and its updates/ revisions; and their repercussions in public higher education, through the counter-reform of the state, especially in the crises of the São Paulo public universities from 2013, focusing on the working conditions of UNESP technical and administrative workers. We conducted qualitative research and document analysis as well as social research, using for these matters dialectical materialism as research method and questionnaires with open and closed questions as data collection technique. We verified in our study the degradation of São Paulo public universities, observed in UNESP case, hitting the precarious working conditions of UNESP technical and administrative workers expressed in the suspension of recruitment and promotion, work overload, imposed versatility, stress, anxiety, lack of recognition and other types of suffering at work, which includes the impact of the neoconservative ideology in the perception of workers about their working conditions, such as immediacy, fragmentation and alienation of themselves and of others. In the same process, we found that those precarious working conditions occurred within a struggling context of the technical and administrative workers. But the constant attack against historically achievedrights and the permanent reality of capitalist exploitation of labor puts on the agenda the need for continued resistance of these workers through collective and autonomous organization